Free-Space Microwave Characteristics of Natural Rubber Composites Filled With Carbon Black for Microwave Application - Ramli, Azlinda (2004)
A contactless and non-destructive microwave method has been developed to characterize natural rubber composites from reflection and transmission measurements made at normal incidence. Microwave non-destructive testing (MNDT) using free-space microwave measurement (FSMM) system involves measurement of reflection and transmission coefficient in free-space. The measurement system consist of a pair of spot focusing horn lens antenna, mode transition, coaxial cables and vector network analyzers (VNA). The inaccuracies in free-space measurements are due to two main sources of errors. 1) Diffraction effects at the edges of the material specimen. 2) Multiple reflections between horn lens antennas and mode transitions via the surface of the sample. The spot-focusing antennas are used for minimizing diffraction effects and we have implemented free space TRL calibration technique by establishing three standards, namely, a through connection, a short circuit connected to each port and a transmission line connected between the test ports. This calibration along with time domain gating feature of the VNA can eliminate effects of multiple reflections.In this method, the free-space reflection and transmission coefficients, S1 and SZ1 are measured for natural rubber composites sandwiched between two Teflon plates of 10.64 mm thickness which act as a half-wave transformer at mid-band. The actual reflection and transmission coefficient, S1 1 and SZ1 of the natural rubber composites are then calculated from measured S1 1 and SZ1 by using ABCD matrix transformation in which the complex permittivity and thickness of the Teflon plates are known. From the complex permittivity, loss tangent, conductivity, wavelength, velocity and skin depth can be obtained. Result for natural rubber composites filled with different concentrations of carbon black are reported in frequency range 9-1 1 GHz.